(untitled) (ОБРАЗОВАНИЕ НАУКА И ИННОВАЦИОННЫЕ ИДЕИ В МИРЕ, 2026)
This article studies non-verbal communication differences between English and Uzbek cultures. The main attention is given to eye contact, gestures, personal distance, touch, facial expression, silence, posture, and voice tone. These signs are important because people do not communicate only with words. A message can be supported, softened, or changed by the body. The article uses comparative, descriptive, cultural, and extract-based analysis. The expected result is to show why English and Uzbek speakers may misunderstand each other in simple daily situations. The novelty of the article is the clear explanation of these differences through short practical examples.